2015
DOI: 10.33687/phytopath.004.01.1074
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Genetic Diversity of Grapevine Leafroll Associated Virus 2 in Algeria

Abstract: Vineyards in western and center regions of Algeria were surveyed for the Grapevine leafroll-associated virus 2 (GLRaV-2). Analyses by DAS-ELISA and Reverse Transcription Polymerase Chain Reaction (RT-PCR) reveal 15, 8% prevalence. The genetic diversity of the GLRaV-2 population was studied by phylogenetic analyses of the HSP70h gene region of seven samples sequenced in this study and other sequences downloaded from GenBank. Results reveal segregation of the GLRav-2 population into six distinct groups. An estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…In this study, we detected GLRaV-2 and GLRaV-3 in agreement with the studies of Lehad et al [ 21 , 22 ]. According to high-throughput small RNA sequencing, GLRaV-1 should be present; however, RT-PCR revealed that the samples were not clearly positive, and detection of GLRaV-1 alone in AL_41 did not clearly identify the PCR product [ 33 ] that could not be clearly established as virus positive.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, we detected GLRaV-2 and GLRaV-3 in agreement with the studies of Lehad et al [ 21 , 22 ]. According to high-throughput small RNA sequencing, GLRaV-1 should be present; however, RT-PCR revealed that the samples were not clearly positive, and detection of GLRaV-1 alone in AL_41 did not clearly identify the PCR product [ 33 ] that could not be clearly established as virus positive.…”
Section: Discussionsupporting
confidence: 93%
“…The survey of GPGV was performed according to the observed symptoms in 54 grapevines in five Algerian regions. In Algeria, there is no clear evidence of the presence of grapevine viruses in the vineyards, except for the surveys of GLRaV-1 [ 20 ], GLRaV-2 [ 21 ] and GLRaV-3 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations